Commission Deductions from Online Food Delivery Sales for MSMEs from the Perspective of Positive Law and Islamic Law - Al Munawar, Faishal Agil; Rohmah, Ainur (Universitas Al-Qolam Malang, 2024)
Indonesia leads the top rank in Southeast Asia in relation to Gross Merchandise Value (GMV) for online food delivery (OFD) services, recording a GMV of US 4.6 billion in 2023. Online food delivery platforms like GoFood, GrabFood, and ShopeeFood have become integral to the lifestyle in major cities, including Malang. These platforms offer consumers convenience when ordering food from various restaurants. However, they also impose commission cuts on every sales transaction to OFD partners, which are often seen as burdensome. This study aims to analyze sales commission cuts on OFD platforms from the perspective of Trade Ministry Regulation Number 70 Year 2019 on Direct Distribution of Goods and the Fatwa DSN-MUI No. 113/DSN-MUI/IX/2017 on Wakalah Bi Al-Ujrah Contract. The method used is empirical juridical with a qualitative approach. The research findings indicate: 1. There needs to be more satisfaction among business operators or OFD partners in Lowokwaru, Malang, regarding the increase in commission cuts. The commission cut mechanisms on the GoFood platform are 20% + Rp. 1,000 per sale, GrabFood is 30% per sale, and ShopeeFood is 25% per sale. 2. According to Trade Ministry Regulation Number 70 Year 2019 on Direct Distribution of Goods, as long as the commission cuts by the three platforms (GoFood, GrabFood, and ShopeeFood) do not exceed 40%, such commission cuts are allowed. Whereas under Fatwa DSN-MUI No. 113/DSN-MUI/IX/2017 on Wakalah Bi Al-Ujrah Contract, commission cuts are permissible provided they meet certain established conditions. Yet, the third condition regarding ujrah has to be fully executed because neither party has agreed on commission increases.